KINERJA PENYULUH PERTANIAN LAPANGAN PADA WILAYAH KERJA BALAI PENYULUHAN PERTANIAN JEMPANG, KABUPATEN KUTAI BARAT (Performance of Agricultural Extension Worker in the Work Area of Agricultural Extension Center of Jempang, Regency of West Kutai) - ELIYYIN ELIYYIN; JURAEMI JURAEMI; MIDIANSYAH EFFENDI (Universitas Mulawarman (University of Mulawarman), 2022)
Agricultural extension is the effort to improve the quality of agricultural human resources, especially farmers, which are one of the tasks of Agricultural Extension Worker (AEW). The purposes of this study were to determine the performance of AEW and farmers perception of the performance of AEW. This research was conducted in the work area of the Agricultural Extension Center (AEC) of Jempang, Jempang Subregency, West Kutai Regency, from May to July 2019. Sampling was carried out in two ways, at the AEW level used the census method, and at the farmers level used the simple random sampling method. This study collected data from interviews with 6 AEW and 44 farmers. Data were analyzed by using descriptive method. The research results showed that the AEW performance in the AEC work area of Jempang was included in the high category (score of 49.3) and farmers perception of AEW performance was included in the positive category (score of 28.27).